The anti-inflammatory scan: current insights and future perspectives on therapeutic splenic ultrasonography - Di Nicolò, Pierpaolo; Corradi, Francesco (The Ultrasound Journal, 2025)
Recent discoveries have identified that physiological anti-inflammatory reflexes are triggered by vagus nerve stimulation (VNS), which offers neuromodulation— performed via implantable or transcutaneous devices— potential therapeutic opportunities. A novel, noninvasive technique using spleen-targeted focused ultrasound stimulation (sFUS) can replicate these effects by triggering the vagus nerve, opening new possibilities for immunomodulation. Early findings suggest that sFUS may evolve into a therapeutic tool to modulate inflammatory responses across a number of diseases. This short communication presents preclinical evidence of efficacy in diverse models of inflammation, discusses the mechanisms underlying sFUS, explores potential translational steps into human application and discusses future directions.